IMPACTO DA CIRURGIA BARIÁTRICA NA URICEMIA E NOS INDICADORES DE RISCO CARDIOVASCULAR EM MULHERES COM SÍNDROME METABÓLICA - Câmara, Thalita de Albuquerque Véras (2014)
Introduction: The association between hyperuricemia and cardiovascular risk factors, especially the metabolic syndrome and his components, has been widely documented. Despite of don t be a treatment directed to hyperuricemia, has been verified that, the bariatric surgery allowed to reach improvements on the acid uric metabolism. Methodology: It was accomplished an retrospective, observational, coorte and analytic study, through secondary data , women s with diagnosed metabolic syndrome according to the criterions of the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III), 2001, underwent to Roux-en-Y gastric bypass mixed technique, in the period of january of 2012 to january of 2014. Of 391 medical records only 84 attempted to the selected sample criterions. It was collected the plasmatic acid uric values, the syndrome metabolic components and otters cardiovascular risk factors. Results: It was noticed a high prevalence of young adult woman s (27 to 34 years), 38,1% (32) , mean age to 33,5±10,1 years, with the mean Body Mass Index (BMI) levels to 39,3±4,3 Kg/m², degree II of obesity occurred with more often in 47,6% (40). The mean of triglycerides (TG) (202,1±92,8 mg/dL), diabetes glucose plasma (135,3±42,6 mg/dL), diastolic e systolic blood pressure, low density lipoprotein (LDL-c) (126,3± 30,5 mg/dL), very low density lipoprotein (VLDL-c) (41,2±19,2 mg/dL) all this data demonstrated an increase when the uric acid levels was ≥ 6 mg/dL, however there was a significant difference only to the variables triglycerides (p=0,0435) , of the hypertensives patients diastolic blood pressure (p=0,0413), and VLDL-c (p=0,0357). The only variable that was positively and significantly correlated (p =0,0026) with the uric acid was the systolic blood pressure, however demonstrated a weak correlation (r=0,3249). And those who presented uric acid level < 6mg/dL and 3, 4 e 5 aggregation of the metabolic syndrome components, the frequency was 100% (43), 77, 8% (21) and 35, 7% (5), respectively, demonstrating reduction of the frequency according with the inclusion of one more syndrome metabolic criteria. And on the cutoff ≥ 6mg/dL, that define hyperuricemia, occurred the opposite, and on the aggregation 4 and 5 the frequency was 22, 2% (6) and 66, 3% (9), and none of the participant with hyperuricemia on the aggregation 3. Conclusion: Surgery for Gastric Bypass Roux-Y was able to reduce the levels of uric acid and cardiometabolic control, including the metabolic syndrome.